Nuchal cord: impact of umbilical artery Doppler indices on intrapartum and neonatal outcomes: a prospective cohort study. (18th October 2019) - Abdallah, A.; Eldorf, A.; Sallam, S.; Ahmed, S.; Shawky, M.; Nawara, M.; El-sayed, M.; Islam, Ba; Abdelrahman, R.; Sabaa, H.; BahaaEldin, A.; Yehia, A.; et al.
Abstract: Background/objective: The purpose of this study is to investigate the use of a more biologic parameter for evaluation of the effect of nuchal cord tightness; the study of blood flow in the umbilical arteries of nuchal cord using Doppler ultrasonography. Methods: This prospective cohort study was conducted at Ain Shams University Maternity Hospital, Cairo, Egypt in the period between August 2015 and August 2017. Hundred primigravidas were recruited with nuchal cord diagnosed by Doppler ultrasonography; whereas the rest of the study population was included in the "Control group". Doppler velocimetry study was then performed on a free-floating loop of the umbilical cord and Doppler indices were calculated. Both groups were followed up during labor: intrapartum events, mode of delivery, and neonatal outcome were recorded. Results: Intrapartum fetal heart rate abnormalities were significantly more common in the nuchal cord group compared to the control group. The overall cardiotocography category was significantly more commonly reflecting abnormal fetal heart rate patterns in the nuchal cord group compared to the control group with 46.74% of the nuchal group patients falling within the "suspicious – pathological – need urgent intervention" categories. Intervention rate was significantly higher in the nuchal cord group than the control group (33.69 versus 21.84%). Moreover, incidence of intrapartum fetal heart rate abnormalities and intervention rate were significantly higher in the nuchal cord with abnormal Doppler subgroup compared to both nuchal cord with normal Doppler subgroup and the control group; with a calculated number needed to harm of 2.11. Conclusions: In view of these results, it might be concluded that umbilical cord tightness affecting fetal hemodynamics (expressed by changes in umbilical artery Doppler) might be a determinate factor affecting the intrapartum course.